NUSUS SYARIAH TERHADAP PENCATATAN PERKAWINAN YANG DIHADAPI MANUSIA YANG SEJALAN DENGAN PERUBAHAN ADAT - adrianto; Sitorus, Chalid (JURNAL MAHASANTRI, 2024)
It cannot be denied that nusus of syari’ah eternal as a scripture Of Allah is absolute Nusus is guidance that covers all aspects human life, individual or society This research uses an approach qualitative method library research The research results show that elasticity of law of syariah which is always based on hikmah and Maslahah al-Ibad. efforts to maintain goals of syariah with maslahah Mu’tabarah, Maslahah Mulghah, and nusus syariah on maslahah in marriage registration is one attempt to realize one of the three of maslahah that exists within humans, namely Daruriyyah, Hajjiyah and Tahsiniyah which is included in the orientation islamic of law pattern“Jalb al-Manfa’ah Wa Daf’u al-Madarrah”, where is the recording? Of marriage with Maslahah Daruriyyah which is included in guarding one of the five things that must be guarded, namely; ad-Din, an-Nafs, al-‘Aql, an-Nasab wa al-Mal.